THE FAMILY DIVERSITY OF PSOCOPTERA AT NUSA PENIDA, KLUNGKUNG DISTRICT-BALI - Toineno, Eyang Sriyani; Watiniasih, Ni Luh; Suartini, Ni Made (Jurnal Biologi Udayana, 2013)
The purpose of the study was to identify diversity of the Psocoptera families collected from Nusa Penida. Samples were collected by beating method. Collected specimens were identified at the Laboratory of Animal Taxonomy, Department of Biology, Udayana University. The results showed that Psocoptera collected from Nusa Penida belongs to 5 families those were: Ectopsocidae, Pachytroctidae, Lepidopsocidae, Pseudocaeciliidae and Hemipsocidae. The genus of Lepidopsocus (Lepidopsocidae) was cosmopolitan, found in all sites: Batu Kandik, Puncak Mundi, Bunga Mekar and Ped. Keywords: insecta, Psocoptera, Nusa Penida.